Cadaveric Length of Trachea in Bangladeshi Adult Male (Bangladesh Journal of Anatomy, 2009)
Context: Anatomical knowledge about length of trachea is essential for anesthetists, surgeons, radiologists & sonologists. In anesthetic procedure, the knowledge of the length of trachea helps to select correct sizes of endotracheal tubes. Study Design: A descriptive type of study. Place and period of study: The study was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka, from July 2006 to June 2007. Materials: 47 trachea of Bangladeshi adult male, age ranged from 20 to 58 years within 24 hours after death which were autopsied in the Department of Forensic Medicine of Sir Salimullah Medical College & Dhaka Medical College, Dhaka. Method: The collected samples were divided into four age groups, ranged from 20 to 58 years and comparative studies were done between different age groups. Result: The length of trachea increased with advancing age. The values showed positive correlation with age & statistically was highly significant (P